Compliance to preventive aspirin therapy in patients after acuter myocardial infarction. ACT Study results - V. M. Gorbunov (Кардиоваскулярная терапия и профилактика)
The ACT Study (Aspirin underutilization and compliance in Cardiovascular diseases Treatment; 2007-2008) was aimed at evaluating the doctors’ views on long-term, low-dose preventive therapy with acetylsalicylic acid (ASA), as well as at developing the strategy on improving patients’ compliance via a specialised questionnaire. The study took place in 18 European, Latin American, and Asian countries. Despite the fact that ASA therapy was recommended to >90 % of the patients after acute myocardial infarction, the treatment compliance was not adequate: for example, good compliance was observed only in 63 % and 54 % of European and Latin American patients, respectively. The most effective measures to increase the patients’ compliance, as reported by the participating physicians, were using the evidence on preventive effectiveness of long-term ASA therapy, and achieving a consensus between a doctor and a patient. Implementation of these measures requires good knowledge of evidence-based cardiology by the doctors, and more “democratic” doctor-patient relationship.